Bounds for degrees of syzygies of polynomials defining a grade two ideal. (March 2023) - Cortadellas Benítez, Teresa; D'Andrea, Carlos; Montoro, M. Eulàlia
Abstract: We make explicit the exponential bound on the degrees of the polynomials appearing in the Effective Quillen-Suslin Theorem, and apply it jointly with the Hilbert-Burch Theorem to show that the syzygy module of a sequence of m polynomials in n variables defining a complete intersection ideal of grade two is free, and that a basis of it can be computed with bounded degrees. In the known cases, these bounds improve previous results.